RELEVANSI EPISTEMOLOGI DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN MATEMATIKA: KAJIAN FILSAFAT ILMU - Khaerani Khaerani (Jurnal Panrita, 2024)
Epistemology, as a branch of philosophy of science that discusses the origins, structure and validity of knowledge, has an important role in developing the mathematics education curriculum. This research aims to explore the relevance of epistemology in designing and implementing a relevant and contextual mathematics curriculum. Using a literature review method based on the philosophy of science, this research analyzes the concept of epistemology in relation to the nature of mathematics, pedagogy and curriculum design. The results of the study show that the application of an epistemological approach in the curriculum is able to increase students' conceptual understanding, build critical thinking skills, and integrate local culture and technology. In addition, this approach encourages learning methods based on discovery and problem solving, which are more effective in facing the challenges of the digital era. Practical implications include designing more meaningful learning, local relevance through ethnomathematics, and strengthening 21st century skills. Thus, the integration of epistemology in mathematics education not only improves the quality of learning but also prepares students to face global challenges with adaptive and innovative thinking skills.